Effects of miR-145-5p on cardiomyocyte proliferation and apoptosis, GIGYF1 expression and oxidative stress response in rats with myocardial ischemia-reperfusion - Liang, Changzai; Wang, Shen; Zhao, Lijing; Han, Yalei; Zhang, Meng (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effects of miR-145-5p on cardiomyocyte proliferation and apoptosis, GIGYF1 expression, inflammation, and oxidative stress in rats with myocardial ischemia-reperfusion injury (IRI). For this purpose, SPF male SD rats were used for IRI modeling. Experimental animals were subjected to specimen sampling and myocardial HE staining. The relative expression of miR-145-5p was detected by qRT-PCR; the protein expressions of GIGYF1, p-AKT, p53, Bax, p38MAPK, and ERK1/2 were detected by Western blot. Mouse embryonic cardiomyocytes H9C2 were used for H/R modeling, which was then subjected to cell transfection according to different grouping protocols. The target of miR-145-5p was confirmed to be GIGYF1 by dual-luciferase reporter assay. Further experiments were performed to detect the survival rate of transfected cells, the apoptosis of transfected cells, SOD activity determination, as well as IL-1β and IL-6 concentrations. The results showed that the expression level of miR-145-5p was downregulated in H2C2 cells (P < 0.05). After 24h of transfection, there was a significant increase in the expression of miR-145-5p in the H/R+miR-145-5p mimic group (P < 0.05), but an evident decrease in the H/R+miR-145-5p inhibitor group (P > 0.05). Compared with the H/R+NC inhibitor group, the H/R+miR-145-5p mimic group had significantly increased cell proliferation, improved release of SOD, and upregulated expressions of ERK1/2 and p-AKT; but downregulated concentrations of IL-1β and IL-6, and decreased expressions of P38MAPK, p53, and Bax (all P < 0.05). Also, the IRI+miR-145-5p agomir group had significantly upregulated expression of miR-145-5p and improved injury degree of heart tissue improved; a significant increase in the protein expressions ERK1/2 and p-AKT, but downregulated protein expressions of P38MAPK, p53, and Bax (all P < 0.05). Dual-luciferase reporter assay identified that GIGYF1 was the target gene of miR-145-5p. Furthermore, through the stimulated overexpression of miR-145-5p, there were significantly increased cell proliferation, improved release of SOD, and upregulated expressions of ERK1/2 and p-AKT; but downregulated concentrations of IL-1β and IL-6, and decreased expressions of P38MAPK, p53, and Bax (all P < 0.05), while the above trends were reversed following the simultaneous upregulation of miR-145-5p and GIGYF1 (all P < 0.05). In general, our study confirmed a decreased expression of miR-145-5p and increased expression of GIGYF1 in the IRI or H/R model in vivo and in vitro. Overexpression of miR-145-5p can downregulate the expression of GIGYF1, further promote cell proliferation, inhibit cell apoptosis, alleviate inflammation and oxidative stress, and hence exert a protective role in myocardial infarction IRI.